Epistemic Decolonization as Overcoming the Hermeneutical Injustice of Eurocentrism - Posholi, Lerato (Philosophical Papers, 2020)
This paper is broadly concerned with the question of what epistemic decolonization might involve. It is divided into two parts. The first part begins by explaining the specifically epistemic problem to which calls for epistemic decolonization respond. I suggest that calls for decolonization are motivated by a perceived epistemic crisis consisting in the inadequacy of the dominant Eurocentric paradigm to properly theorize our modern world. I then discuss two general proposals, radical and moderate, for what epistemic decolonization might involve. In the second part, I argue that the inadequacy of Eurocentric epistemic resources constitutes a hermeneutical injustice caused by an irreducible form of epistemic oppression. I then argue that addressing this form of epistemic oppression requires thinking ‘outside’ of the Eurocentric paradigm because the paradigm might fail to reveal and address the epistemic oppression sustaining it. This lends further plausibility to the radical proposal that epistemic decolonization must involve thinking from ‘outside’ the Eurocentric paradigm, but also accommodates the moderate proposal that adopting critical perspectives on Eurocentric thought is an important part of epistemic decolonization.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; discours dominant; décolonisation épistémique; fem9000; féminisme décolonial; injustices herméneutiques; injustices épistémiques; philosophie; sciences humaines; système colonial; systèmes d'oppressions; thématiques; violences; études décoloniales

Je suis un monstre qui vous parle: rapport pour une académie de psychanalystes - Preciado, Paul B. (Grasset, 2020)
« La psychanalyse est face à un choix historique sans précédent : soit elle continue à travailler avec l'ancienne épistémologie de la différence sexuelle et légitime de facto le régime patriarco-colonial qui la soutient, devenant ainsi responsable des violences qu'elle produit, soit elle s'ouvre à un processus de critique politique de ses discours et de ses pratiques. Continuer à pratiquer la psychanalyse en utilisant la notion de différence sexuelle, avec des instruments cliniques comme le complexe d'OEdipe, est aussi aberrant que de prétendre la terre plate. Le temps est venu de sortir les divans sur les places, collectiviser la parole, politiser les corps, débinariser la sexualité et décoloniser l'inconscient : la survie de la psychanalyse est à ce prix. »-- Quatrième de couverture.
Keywords: approches et analyses; corps; cours; cycles supérieurs; discipline; discours dominant; fem7000; identités LGBTQIA2+; patriarcat; personnes trans*; sciences humaines; systèmes d'oppressions; thématiques; violences; épistémologie